PENGETAHUAN TERHADAP PERILAKU PERAWATAN KESEHATAN GIGI DAN MULUT PADA ANAK USIA 9-12 TAHUN DI SDN 27 PEMECUTAN DENPASAR - Carla Dianmartha; Sari Kusumadewi; Desak Putu Yuli Kurniawati (Odonto : Dental Journal, 2018)
Background: One of the factors that can affect oral health is health behavior. One of the predisposing factors that influence behavior is knowledge. A person who is aware of the importance of oral health can be seen from their knowledge. The aim of this study is to determine the relationship between dental knowledge with their oral health care behavior in children age 9-12 years at SDN 27 Pemecutan Denpasar.Methods: Observasional research used cross sectional approach. The respondent in this research are 87 children age 9-12 years at SDN 27 Pemecutan Denpasar. The samples were taken by using systematic random sampling technique and questionnaire as the measuring instrument to know the level of dental knowledge and dental health care behaviour. Processing technique and data analysis used chi square statistic test.Results: The result of this research showed that the respondent who have ahigh level of knowledge had good behavior is 63,9%. Low knowledge level with less behavior was 80,8%. Respondents have good behaviour if the score of the questionnaire mean total value of questionnaire and respondents less behaviour if the score of the questionnaire < mean total value of questionnaire.Conclusions: It can be concluded there is a significant relationship between dental knowledge and oral health care behavior in children aged 9-12 years in SDN 27 Pemecutan Denpasar.